Curing Dynamics of Soy Flour-Based Adhesives Enhanced by Waterborne Polyurethane - Yong Wang; Xianjun Li; Wanli Lou; Layun Deng; Youhua Fan (International Journal of Polymer Science)
In this paper, thermogravimetric (TG) analysis was carried out to make clear the curing properties of soy flour-based adhesives (SFAs) enhanced by waterborne polyurethane (WPU) with different addition levels. The kinetic parameters were evaluated by a thermal dynamics method, including activation energy and preexponential factor. In addition, the structure characteristics of both soy flour and modified soy flour-based adhesives were tested by Fourier transform infrared spectroscopy (FTIR). The results revealed that the FTIR spectra of pristine soy flour-based adhesives were different from those of soy flour after alkali treatment and waterborne polyurethane modification. Furthermore, there were four main degradation phases in the derivative thermogravimetric (DTG) curves of modified soy-based adhesives while there were two phases of a defatted soy flour sample. The kinetics analysis demonstrated that the curing process could be described as a consecutive first-order curing process. Moreover, with the addition level of WPU growing, the apparent activation energy of each phase of the curing process was increasing compared with that in pristine soy-based adhesives.